Adolescents’ Mental Health at School: The Mediating Role of Life Satisfaction - Cavioni, Valeria; Grazzani, Ilaria; Ornaghi, Veronica; Agliati, Alessia; Pepe, Alessandro (Frontiers in Psychology, 2021)
In this study, we further developed prior research on risk and protective factors in adolescents’ mental health. More specifically, we used structural equation modelling to assess whether relationships at school with teachers and peers, and life satisfaction predicted mental health in a large sample of adolescents, while also testing for age and gender invariance. The sample comprised 3,895 adolescents (Mage= 16.7, SD = 1.5, 41.3% girls), who completed self-report instruments assessing their perceived life satisfaction, student-teacher relationships, school connectedness, and mental health. Overall, the results suggested that life satisfaction acted as a mediator between adolescents’ positive school relations and their mental health. Outcomes were invariant across genders, while the quality of school relations and mental health declined with age. Limitations of the study and futures lines in mental health research among adolescents are briefly discussed.